Inhibition of platelet aggregation by bovine endocardial apyrase. - Yi Fu-xian; Huang Shao-ling; Guo Xun; Sun Ping; Guo Zhao-gui (Acta Pharmacologica Sinica, 2016)
AIM: To study the anti-aggregatory effect of bovine endocardial endothelial cell (EEC)-associated apyrase. METHODS: Cultured bovine EEC was used. Adenosine diphosphate (ADP) was analyzed by reversed phase HPLC, and rabbit platelet aggregation was measured turbimetrically. RESULTS: Incubation of EEC with ADP 500 mumol.L-1 resulted in a progressive decrease in ADP concentration, which was paralleled by the decrease in platelet aggregating potential of the unmetabolized ADP. In the presence of aspirin (Asp 1 mmol.L-1)-treated EEC 1 x 10(9) cells.L-1, the aggregation of Asp (1 mmol.L-1) and methylene blue (10 mumol.L-1)-treated platelets in response to thrombin 500 U.L-1 and platelet activating factor (PAF 1 nmol.L-1) was markedly inhibited and was reversible, which was very similar to that in apyrase-treated platelets. The supernatants of EEC had no effect on platelet aggregation. EEC inhibited ADP (5 mumol.L-1)-induced platelet aggregation, but failed to inhibit adenosine 5'-O-(2-thiodiphosphate) (ADP-beta-S, an unmetabolizable structural analog of ADP, 15 mumol.L-1)-induced platelet aggregation. CONCLUSION: ADP hydrolysis by EEC-associated apyrase is a major anti-thrombotic mechanism of bovine EEC.